Aplicación de las técnicas de creatividad y su relación con el aprendizaje del dibujo técnico: proyecciones y vistas, en los estudiantes del tercer semestre de la Escuela de Ciencias, carrera de Ciencias Exactas, durante el período septiembre 2013 – octubre 2014 - Shagñay Ñamo, Jessica Elizabeth (2016)
This research aimed to analyze the application of creativity techniques and their relationship with learning Technical Drawing: Projections and Views, in students of the third semester of the School of Sciences, career of Exact Sciences during the period September 2013 - October 2014. It is a transversal study of explanatory type, because it took care to explain how creativity techniques are related to the learning of technical drawing. We have worked with a total population of 14 people between teachers and students, for the small size of the universe it was not necessary to obtain a sample. As a research tool the survey and observation guide were used the same that allowed us to obtain the required information. After obtaining results were identified that students did not apply creativity techniques in the classroom so it was necessary the development and implementation of a guide. In conclusion, the guide was a valuable tool that allowed us to stimulate learning new techniques of creativity in students and encourage learning of technical drawing. It is recommended to teachers to promote the guide as a tool for practicing and learning technical drawing